Geostrategic Essence of the Bay of Bengal & Its Implications on the Energy Security: A Bangladesh Perspective - Md. Aslam Hossain Jony; Shiblee Nomani (CV. Literasi Indonesia, 2021)
The Bay of Bengal has received huge interest from global powers after the Second World War. The rivalry between India and China exists for decades. The research aims to showcase the Geostrategic essence of the Bay of Bengal and its implication on energy security through the perspective of Bangladesh. The paper also focuses on the complexities created on energy security by Sino-Indian rivalry and vice versa along with the challenges for Bangladesh’s energy security as well as regional peace and harmony. Finally, the research paper would employ its analysis to illustrate some possibly reliable recommendations to mitigate the complexities of energy security in the Bay of Bengal region.